Early Response of Sulfolobus acidocaldarius to Nutrient Limitation - Bischof, Lisa F.; Haurat, M. Florencia; Hoffmann, Lena; Albersmeier, Andreas; Wolf, Jacqueline; Neu, Astrid; Pham, Trong Khoa; Albaum, Stefan P.; Jakobi, Tobias; Schouten, Stefan; Neumann-Schaal, Meina; Wright, Phillip C.; et al. (Frontiers in Microbiology, 2019)
In natural environments microorganisms encounter extreme changes in temperature, pH, osmolarities and nutrient availability. The stress response of many bacterial species has been described in detail, however, knowledge in Archaea is limited. Here, we describe the cellular response triggered by nutrient limitation in the thermoacidophilic crenarchaeon Sulfolobus acidocaldarius. We measured changes in gene transcription and protein abundance upon nutrient depletion up to 4 h after initiation of nutrient depletion. Transcript abundance of 1118 of 2223 protein coding genes and levels of approximately 500 proteins with functions in almost all cellular processes were affected by nutrient depletion. Our study reveals a significant rerouting of the metabolism with respect to degradation of internal as well as extracellular-bound organic carbon and degradation of proteins. Moreover, changes in membrane lipid composition were observed in order to access alternative sources of energy and to maintain pH homeostasis. At transcript level, the cellular response to nutrient depletion in S. acidocaldarius seems to be controlled by the general transcription factors TFB2 and TFEβ. In addition, ribosome biogenesis is reduced, while an increased protein degradation is accompanied with a loss of protein quality control. This study provides first insights into the early cellular response of Sulfolobus to organic carbon and organic nitrogen depletion.